A low‐profile planar end‐fire broadband antenna with wide beamwidth. Issue 5 (8th February 2023) - Xue, Hui; Shen, ZhiXin; Wu, Li; Rong, Yingjiao; Peng, ShuSheng
Abstract: A low‐profile planar end‐fire broadband antenna with wide beamwidth is presented. The proposed antenna consists of a grounded coplanar waveguide (GCPW), an antipodal dipole, and a pair of directors. A transition from the GCPW to the substrate integrated waveguide (SIW) with tapered coupling slots is designed to achieve a wide impedance bandwidth. Wide beamwidths of the proposed antenna are realised through the antipodal dipole with bilaterally symmetrical sector arms. A pair of directors are symmetrically located on both sides of the sector arms to further widen the beamwidth. An antenna prototype operating at Ka band with a size of 2.18 λ 0 × 0.77 λ 0 × 0.06 λ 0 ( λ 0 is the wavelength of the centre frequency) is fabricated based on the conventional printed circuit board process. The measurement results show that the reflection coefficient is lower than −12.5 dB in the frequency range of 32.2–37.0 GHz. At 35.5 GHz, the peak gain is 3.8 dBi, and the half‐power beamwidths (HPBWs) in E ‐plane and H ‐plane are 116° and 215°, respectively. Abstract : A low‐profile planar end‐fire broadband antenna with wide beamwidth is presented. The design of the grounded coplanar waveguide lays the foundation for achieving broadband, and the combined action of the antipodal dipole and the directors broadens the beamwidth of the proposed antenna. The measured results reveal that the relative bandwidth of the antenna is 23.4% (31.8–40.0 GHz), and the half‐power beamwidths of E‐plane and H‐plane at 35.5 GHz are 116° and 215°, respectively.